The great narwhal rescue : saving the Arctic ocean's narwhals - Markle, Sandra (Sandra Markle's science discoveries, 2025)
"Narwhals have lived in the icy Arctic Ocean for centuries. But as temperatures rise, ice disappears, and humans venture into the Arctic, these animals are in danger. Discover how scientists are working to protect narwhals"-- Provided by publisher.